THEORETICAL BASIS OF LOCAL BUDGET EXPENDITURES AS AN INSTRUMENT OF FISCAL POLICY AND A COMPONENT OF PUBLIC FINANCE (INNOVATIVE ECONOMY, 2024)
Lobodina Z.M., Demianyshyn V.Н., Chernyshenko Yu.O., Vitresku I.P. THEORETICAL BASIS OF LOCAL BUDGET EXPENDITURES AS AN INSTRUMENT OF FISCAL POLICY AND A COMPONENT OF PUBLIC FINANCEPurpose. The purpose of the article is to substantiate the theoretical foundations of local budget expenditures as an instrument of fiscal policy and a component of public finances.Methodology of research. The research is based on the use of scientific developments of financiers on the issues of local finance, budgeting and regional policy. For the scientific understanding of the theoretical basis of local budget expenditures as a financial instrument and a component of public finance, the research used special and general scientific methods – analysis, synthesis, scientific abstraction, systematization, argumentation, in particular: dialectical, monographic, analysis and synthesis – to study the theoretical basis of local budgets; dialectical approach – to interpret the concept of “local budget expenditures”; graphical – to visually display the content of the phenomena and processes under study; abstract and logical – in the formation of theoretical generalizations, assumptions, and conclusions.Findings. The economic essence is revealed and, based on the use of methodological tools of modern financial science, a comprehensive theoretical and methodological approach to the disclosure of the essence of «local budget expenditures» is formed. The functional purpose of local budget expenditures is clarified. The expediency of adherence to the principles of local budget expenditures is argued and the most important of them are highlighted. The modern forms of budget financing are characterized, which made it possible to systematize the types of local budget expenditures depending on the forms of their implementation. The author proposes approaches to solving an important problem of local self-government bodies - lack of full budgetary resources for the provision of public services.Originality. The theoretical principles of spending local budgets in the conditions of public finance reform are summarized. Based on the use of the methodological tools of the dialectical approach to understanding the essence of local budget expenditures, a comprehensive approach to this definition is formulated. The authors have improved scientific approaches to identifying the functional purpose of local budget expenditures, principles and forms of their implementation.Practical value. The substantiated conclusions and proposals made it possible to develop the conceptual apparatus of financial science, to improve the theoretical and methodological approaches to the implementation of local budget expenditures. Implementation of the proposals on the expediency of distinguishing in the Budget Code of Ukraine between local budget expenditures for the implementation of delegated and own powers of local governments and specifying the sources of financial support for these types of powers will help to ensure that public services are fully funded.Key words: budget expenditures, local budget expenditures, public finance, principles of budget expenditures, forms of budget expenditures, estimated financing, transfer financing, financial resources of local governments, fiscal policy.
Keywords: budget expenditures; local budget expenditures; public finance; principles of budget expenditures; forms of budget expenditures; estimated financing; transfer financing; financial resources of local governments; fiscal policy.